KAJIAN SIFAT FISIK, KIMIA, DAN SENSORI FRUIT LEATHER BELIMBING WULUH (Averrhoa billimbi L) DENGAN PENAMBAHAN PEMANIS RENDAH KALORI STEVIA (Stevia rebaudiana) - Nopiani, Yanti; Purwaningtyas, Ratna Yuniar; Mursyid, Harsanto; Pramana, Angga (Program Studi Teknologi Pangan, 2022)
Fruit leather is made from a mixture of crushed fruit (puree) were dried at 70°C for 8 until 15 hours with a thickness ranging from 2-3mm and commonly being consumed directly as a snacks. Belimbing wuluh contains 25mg of vitamin C and several nutrient contains, but it consumption is still low because of the sour taste. Belimbing wuluh is only used as an additional ingredient for cooking. Belimbing wuluh can be used as raw material of fruit leather as a snack to increase the consumption and economic value. The stevioside extract is being added to cover the sour taste and the alternative low calorie sweetener.The purpose of the study was to determine the effect of the concentration of stevioside as a sweetener in low calorie (0%; 0.05%; 0.10% and 0.15%) based on the characteristics of the physical, chemical, and sensory fruit leather. The research uses one factor of Completely Randomized Design (CRD) wich is variation increasing of stevioside extract (0%; 0,05%; 0,10%; 0,15%). The result showed that steviosie extract has no effect on the texture (hardness), water content, and vitamin C, but it influences to the total dietary fiber and total calorie. The addition of extracy stevioside does not influence to the color, aroma, texture but influential the taste. The higher the concentration of extract stevioside given the fruit flavors are increasingly favored leather panelists however leave a bitter aftertaste. Samples of fruit leather is most preferred by consumers is fruit leather belimbing wuluh with the addition of stevia 0.15% (hardness = 1592gf; water content = 21%; vitamin C = 18.040; total calories = 3.612 kcal / g; total dietary fiber = 10.490%) is a formulation that has the potential to make Averrhoa billimbi L fruit leather.